The development of potential performance in ski jumping from the morphological and motoric aspect - Jost, B.; Ulaga, M.; Vodicar, J. (Science and Skiing VII, 2018)
With the standard expert system sports manager, it was possible to determine the state of general longitudinal development of the reduced potential competitive performance (RPCP) in the morphological and primary motoric space. Morphological development of ski jumpers is fairly rapid and the athletes can achieve an excellent score of the reduced potential competitive performance already between 15-and 17-year-olds. The first peak in development of motoric skills is generally achieved at the end of the youth age category at age 20. In general, the developmental curve may increase slightly for individuals up to 25 years of age. The expert system provides an insight into the longitudinal status of a ski jumper`s reduced potential performance. The selected best Slovenian athletes showed very high levels of reduced potential competitive performance, as well as actual competitive performance.